The legal system of Louisiana under French colonial rule from 1699 to 1769 - Szymańska, Aleksandra; Szymura, Mateusz (Studia Iuridica Toruniensia, 2020)
The subject of the paper is an attempt to show the legal system of Louisiana in its first period of operation – first as a trading colony administered by the French merchant Antoine Crozat and the Scottish financier John Law, and then as a royal domain, which Louisiana was until 1769. The diversity of the local legal systems of pre-revolutionary France was impossible to implement in the legal framework of the French colonies, and therefore it was decided to apply in Louisiana the universally applicable laws in the form of Grand Ordinances and the law of the local region of Île-de-France – La Coutume de Paris. The legal system of the colony was not the same as the legal system of the European capital, as evidenced by the regulations created directly for the overseas territories. The best known example of such a legal act was the Ordonance of Louis XIV from 1685. (Code Noir), which regulated slavery in French colonies. The authors argue that, despite the lack of reception of the Napoleonic Code in Louisiana, elements of the French legal tradition were an impor tant factor in building and consolidating the civilian element, which still distinguishes the legal system of the American state of Louisiana from that of other members of the Union.